ETHNOBOTANICAL STUDY OF MANGROVES FROM COASTAL COMMUNITIESOF BUNAKEN NATIONAL PARK, INDONESIA - Nova Laurin Isye Mourein Ogi; Fernando A Watung; Mercy M Rampengan; Meisa Tabita Rogahang; Verawati Ida Yani Roring; Mokosuli Yermia Semuel (SEAMEO BIOTROP, 2026)
ARTICLE HIGLIGHTSMangrove species like Acanthus ilicifolius and Avicennia marina aid food and health.Correlation and PCA reveal food, medicine, and firewood as key use dimensions.Location trends: Sondaken for firewood, Baboi for medicine, Mantehage for knowledge.This study supports mangrove ethnobotany and promotes community bioconservation.ABSTRACTMangrove ecosystems play a vital ecological and socio-economic role along coastal regions. However, their sustainable utilization faces significant challenges due to habitat degradation and modernization. This study aimed to characterize the ethnobotanical utilization of mangroves by coastal communities within Bunaken National Marine Park (BNMP) and its surrounding small islands, while exploring their potential for food and medicinal bioprospecting. Data were collected through questionnaire surveys, in-depth interviews with informants, and field observations within coastal communities in four locations such as Bahoi, Likupang Barat District, North Minahasa, Sondaken, Tatapaan District, South, Alung Banua, Bunaken Archipelago District, Manado, and Mantehage, Wori District, North Minahasa Regency. The data were subsequently analyzed descriptively, followed by Principal Component Analysis (PCA) and heatmap visualization. The findings revealed that specific species such as Acanthus ilicifolius and Avicennia marina occupy central roles as sources of food and traditional medicine, emphasizing the close integration between subsistence needs and community health. Correlation analysis and PCA indicated that the categories of food, medicine, and firewood represent the dominant dimensions of utilization, while cultural functions and species knowledge serve as secondary differentiators. Location-based variations underscored the heterogeneity of utilization practices, with Sondaken being more prominent in firewood use, Bahoi in ethnomedicine, and Mantehage in biodiversity knowledge. These findings highlight the necessity of mangrove management that extends beyond ecological conservation to include local wisdom as a foundation for bioprospecting, thereby supporting food security, health, and the well-being of coastal communities. Thus, this research significantly contributed to the literature on mangrove ethnobotany and provided a scientific framework for community-based bioconservation strategies in Indonesia.